Human rights and media - Papademas, Diana (Bingley, U.K. : Emerald, 2011)
Volume 6 on'Human Rights and Media' introduces and analyzes the significant relationship and discourse of human rights and media. As agenda setters, framers and integral actors in human rights movements, various forms of media are analyzed by the contributing authors. News media, the press, television, cinema, photojournalism, the internet and other documentary forms are among the media investigated by the authors. Civil society dialogue, the rhetoric and ideology of human rights, the propaganda and media responsibility around such themes as war, genocide, ethnic division, nationalism, race, gender, child labor and disability are human rights themes addressed in this volume.
Introduction : human rights and media / Diana Papademas -- Toward a sociology of human rights / Mahin Gosine -- The Council of Europe's human rights : perspective on the media / Sam Cherribi -- The rhetoric and ideology of human rights in the media / Josh Klein -- War making and propaganda : media responsibility for human rights communication / David L. Altheide, Jennifer N. Grimes -- Recognition of genocide in Bosnia : frameworks of interpretation in U.S. newspapers / Helen Fein, Walter Ezell, Herbert F. Spirer -- National and ethnic discourses on Cyprus television / Nayia Roussou -- Human rights discourse in the Antebellum black press / Timothy Shortell -- Child labor and photojournalism / Edoardo Gianotti -- Internet, computer-mediated communications and gay rights movements in Taiwan / Chung-Yi Cheng, Kenneth C.C. Yang -- Disability and the media in the 21st century / Doris Zames Fleischer, Frieda Zames.
Keywords: Mass media; Human rights